DETERMINANTS OF BANKS’ PROFITABILITY – EVIDENCE FROM GO PUBLIC BANKS IN INDONESIA - Natalia, Clarisa Nesya; Wirianata, Henny (Graduate Program of Universitas Tarumanagara, 2023)
Bank performance needs to be monitored because of the role of banks as intermediary institutions that collect funds from surplus parties and channel them to deficit parties. This business characteristic makes the banking sector regulated by the government to maintain economic stability and meet the interests of society. Banking performance during 2018-2022 is engaging to study because there is a significant force, namely the COVID-19 pandemic, which impacts economic stability in Indonesia. This research was conducted to obtain empirical evidence of the influence of banking-specific factors and industry-specific factors on banking performance. This research uses quantitative methods by collecting financial reporting data from companies in the banking sub-sector. The banking-specific factors that influence bank performance are capital measured by CAR, liquidity measured by CDR, firm size measured by bank size, asset quality measured by NPL, cash ratio, leverage measured by the DER, management productivity measured by the BPE and the industry-specific factors that influence bank performance, namely GDP, inflation rate and effective tax rate. ROA measures banking performance. Data collection and processing were carried out using IBM SPSS Statistics 25 software. The study's results showed the banking-specific factors that significantly influenced bank performance were CDR, bank size, NPL, DER, and BPE. In contrast, the industry-specific factor was only GDP, which significantly influenced banking performance.